2012
DOI: 10.1111/j.1467-3010.2012.01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer understanding of sugars claims on food and drink products

Abstract: Consumer understanding of nutrition and health claims is a key aspect of current regulations in the European Union (EU). In view of this, qualitative and quantitative research techniques were used to investigate consumer awareness and understanding of product claims in the UK, focusing particularly on nutrition claims relating to sugars. Both research methods identified a good awareness of product claims. No added sugars claims were generally preferred to reduced sugars claims, and there was a general assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 4 publications
4
26
0
Order By: Relevance
“…These findings are largely in line with consumer perceptions that sweeteners would be used to replace sugar in products with sugar claims (Patterson et al 2012). Sweetener use may also explain the lower proportion of products with sugar claims that had excess free sugar levels.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These findings are largely in line with consumer perceptions that sweeteners would be used to replace sugar in products with sugar claims (Patterson et al 2012). Sweetener use may also explain the lower proportion of products with sugar claims that had excess free sugar levels.…”
Section: Discussionsupporting
confidence: 74%
“…Second, another area of concern from a public health perspective is that most products with sugar claims were lower in free sugar contents, but the reduction was not comparable for calories. Consumer research has shown that consumers expect similar and meaningful calorie reductions in products with sugar claims (Patterson et al 2012). This finding highlights a misalignment between consumer perceptions and regulatory requirements.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…'Fan' pages on Facebook are an example of such communities, and form the basis for our study presented in this paper. Existing research has examined consumer interactions in online communities ( [7]), social network based communities for promoting engagement with a brand ( [22,8]), consumer motivations for participation, and effective means for developing consumer-brand relationships ( [30]). The topic of brand-brand relationships, however, has not received much attention in the literature -this is the focus of our study, using large-scale data, sentiment analysis and network analysis.…”
Section: Related Workmentioning
confidence: 99%
“…The subject of consumer understanding of nutrition and health claims is explored in a paper in this issue of Nutrition Bulletin by Patterson et al . (2012, pp.…”
mentioning
confidence: 99%